1974
DOI: 10.1042/bj1390043
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and inactivation of superoxide dismutase by hydrogen peroxide

Abstract: Reactions of H(2)O(2) with superoxide dismutase were studied by e.p.r. (electron paramagnetic resonance) spectroscopy and other methods. In agreement with earlier work, the Cu(2+) of the enzyme is reduced by H(2)O(2), although the reaction does not go to completion and its kinetics are not simple. With dilute enzyme the time for half-reduction with 9mm-H(2)O(2) is about 150ms. It is suggested that the reaction is a one-electron reduction, involving liberation of O(2) (-). On somewhat more prolonged exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
136
1
2

Year Published

1977
1977
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 372 publications
(153 citation statements)
references
References 18 publications
13
136
1
2
Order By: Relevance
“…9 F. LAVELLE ANI) OTHERS signals were seen (cf. bovine Cu-superoxide dismutase; Bray et al, 1974). Hachimori et al (1964 have shown that H202 reacts with aromatic amino acids, either in free solution or as residues in proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 F. LAVELLE ANI) OTHERS signals were seen (cf. bovine Cu-superoxide dismutase; Bray et al, 1974). Hachimori et al (1964 have shown that H202 reacts with aromatic amino acids, either in free solution or as residues in proteins (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, this reaction mechanism may not be simple and the second-order rate constant quoted may apply only under the stated conditions (cf. bovine erythrocyte enzyme; Bray et al, 1974).…”
Section: Reduction and Inactivation By H202mentioning
confidence: 99%
“…H202 has been proposed to inactivate Cu,Zn-SOD by causing the hydroxylation of a copper-ligating histidine [40,41]. This results in a reduced metal affinity and, consequently, in the detachment of copper [42].…”
Section: Effects Of Copper On the Growth Of K562 Cellsmentioning
confidence: 99%
“…The most accepted hypothesis of aging was proposed by Gerschman [15] and Harman [1] who suggest that aging results from the accumulation of damage caused by free radicals; this is supported with evidence found by different systems [16][17][18][19][20][21]. The use of strains deficient in the expression of endogenous antioxidants has been practicable in testing the effect of dietary antioxidants in lifespan.…”
Section: Introductionmentioning
confidence: 75%
“…Drosophila melanogaster has been extensively used to test the effect of dietary exogenous antioxidants in lifespan because it offers many advantages: its lifespan is short, 80 -90 days (in laboratory conditions) and no mitotic divisions take place in the adult [22]. In addition, different mutant strains in genes involved in antioxidant defense such as catalase and superoxide dismutase enzymes could be used [16,20]. It is known that through the lifespan of Drosophila the activity of Cat decreases [18,[23][24][25] however, the increased expression of the Cat gene does not extend the lifespan of flies, but rather protects against oxidative stress [26].…”
Section: Introductionmentioning
confidence: 99%